The role of Argopecten purpuratus shells structuring the soft bottom community in shallow waters of southern Peru - Lomovasky, Betina Judith (2015)
Accumulation of Argopecten purpuratus shells often occurs after El Niño events in shallow waters of Independencia Bay (14°17'S-76°10'W; Pisco, Peru). Here we experimentally investigate the effects of their shell accumulation on macrobenthos assemblages in soft bottom, shallow areas of the bay. A field experiment (from May 2006 to May 2007), including four treatments with different coverage levels of empty shells of A. purpuratus, were randomly arranged in: (1) areas devoid of shells ("Empty" treatment: experimental control), (2) 50% of the plot area covered with shells haphazardly distributed over the bottom ("medium" treatment), (3) 100% of the plot area covered with shells, forming a 10 cmvalve layer ("full" treatment) and (4) "natural control". We found a total of 124 taxa throughout the experiment. Polychaetes, crustaceans and mollusks were the most abundant groups in "natural controls", dominated by the gastropod Nassarius gayi and the polychaetes Prionospio peruana, Platynereis bicanaliculata and Mediomastus branchiferus. The abundance of individuals (N) and the species richness (S) were higher in the "medium" treatment, but only in one month under positive sea bottom thermal anomalies. Similarity analysis (Bray-Curtis) showed that "natural control", "empty" and "full" treatments were more similar among them than the "medium" treatment. Multidimensional analysis showed no clear species association among treatments and a higher grouping among the samplings of Jun-06, Aug-06 and Nov-06. Our results also showed that the commercial crab Romaleon polyodon and the polyplacophora Tonicia elegans were positively affected by shell accumulations ("medium" treatment), while the limpet Fissurella crassa was negatively affected. Our study shows that directly by changing habitat structure or indirectly by changing sediment characteristics, the addition of scallop shells to the soft bottomcan modify the macrobenthic assemblage however, the seasonal oceanographic variability (e.g. upwelling, El Niño) could have stronger effects controlling this system than the presence of the shells itself.